PEMUNCULAN SELF DISCLOSURE DALAM RELASI FRIEND WITH BENEFIT (Studi Fenomenologi Perempuan Muda Surabaya) (Universitas Negeri Surabaya, 2023)
The research aims to find out how the self-disclosure process of young Surabaya women who are involved in Friend With Benefit (FWB) relationships is based on Joseph DeVito's self-disclosure theory which is associated with social penetration theory. This research is a qualitative research with phenomenological methods. Data collection techniques in this study used interview techniques and documentation. The results obtained in this study are the background factors of informants' meetings with their FWB partners and also the purpose of establishing FWB relationships affect the level of self-disclosure of informants. This causes phases to be created in the process of self-disclosure which means according to the theory of social penetration. In the theory of social penetration, there are stages that determine the depth of self-disclosure that is carried out, this is also found in research informants, informants have various phases of the self-disclosure process that they do. Topics disclosed as self-disclosure to their FWB partners include aspects of background, health, hygiene, individual goals, feelings, desires, sexual fantasies and privacy. In more intimate relationships, self-disclosure already includes more complex matters such as sexual exploration, being able to feel comfortable, being able to better understand and build trust in one another.